Eating disorders. - Fairburn, C; Harrison, P (2003)
Eating disorders are an important cause of physical and psychosocial morbidity in adolescent girls and young adult women. They are much less frequent in men. Eating disorders are divided into three diagnostic categories: anorexia nervosa, bulimia nervosa, and the atypical eating disorders. However, the disorders have many features in common and patients frequently move between them, so for the purposes of this Seminar we have adopted a transdiagnostic perspective. The cause of eating disorders is complex and badly understood. There is a genetic predisposition, and certain specific environmental risk factors have been implicated. Research into treatment has focused on bulimia nervosa, and evidence-based management of this disorder is possible. A specific form of cognitive behaviour therapy is the most effective treatment, although few patients seem to receive it in practice. Treatment of anorexia nervosa and atypical eating disorders has received remarkably little research attention.